KINERJA MARSHALL CAMPURAN BERASPAL PANAS LAPIS (AC-BC) MENGGUNAKAN LIMBAH BETON - Galih Wulandari Subagyo; Indramaha Indramaha (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2019)
In a State infrastructure development is needed for the progress of a nation. This is very important. It should be seen in terms of social, economic, and also have a positive interest because they have to increase development and economy. However, in the past will require new material. One effort to getnew material is by mining sand or rock from the volcanic lava flow deposits. The aforementioned issues are a strong driver in the development of asphalt pavement technology to obtain durable, inexpensive and environmentally friendly pavements including in Indonesia, which helps minimize the existence of natural destruction, one of which is related to using water material for paving new roads has done a lot. One of the waste materials that will be tried to be replaced by new aggregates in this study is concretewaste. variation of concrete waste of 0%, 5%, 10%, 15% of the total new aggregate. Then testing the object of the test with the Marshall test method obtained results of Marshall characteristics on the test. Based on the results of the study, the use of concrete waste as coarse aggregate on Marshallkararteristic values in the AC-BC mixture. The greater absorption of concrete waste causes asphalt to be absorbed more than when mixed without using concrete waste. From the analysis results obtained negative values, VMA, VIM and Marshall Quotient increase the increase, while the flow value and VFB increase decrease with increasing levels of concrete waste. The highest value was obtained at 15% concrete waste content that is 1807.1kg, the highest VMA value was obtained at 15% waste content that was 18.81%, the greatest VIM value was obtained at 15% concrete waste content level that was 10.06%, Marshall value The highest was obtained at 5% concrete waste content which was 748.70kg /mm, the highest flow value was obtained at 15% concrete waste content which was 5.82mm and the highest VFB value was obtained at normal levels that was 99.91%.